Influence of Erbium, Cerium on the Stress Corrosion Cracking Behavior of AZ91 Alloy in Humid Atmosphere1 . Issue 7 (5th April 2017) - Song, Yulai; Wang, Zhen; Liu, Yaohui; Yang, Miao; Qu, Qingxiang
Abstract : AZ91 magnesium alloys modified by Er and Ce are fabricated (referred to as AZErCe) and their stress corrosion cracking (SCC) behaviors are studied by slow strain rate tensile (SSRT) method in air, humid atmosphere with and without chloride. The addition of Er and Ce promotes the formation of Al3 Er and Al11 Ce3 phase and reduces both the size and the volume fraction of β‐phase. AZErCe possess improved corrosion resistance and passivation characteristic compared to AZ91 due to the reduced micro‐galvanic corrosion and the more protective films. SSRT tests demonstrate that the joint addition of Er and Ce effectively improve the SCC resistance of AZ91 alloy. In particular, the representative fractography of AZErCe exhibits lesser effect of hydrogen embrittlement than AZ91. The improved SCC resistance of AZErCe can be ascribed to the presence of Er and Ce, which alleviate corrosion of Mg matrix and thus weaken the effect of hydrogen embrittlement on SCC resistance. Abstract : Compared with the microstructure of as‐cast AZ91 alloy, the addition of Er and Ce can significantly reduce the volume fraction and the size of β ‐phase and facilitate the formation of Al3 Er and Al11 Ce3 intermetallic compounds, which are easily distinguished by white color from gray β ‐phase. All of these changes exert positive effect on SCC resistance of AZ91 alloy.